2006
DOI: 10.1002/jbm.a.30893
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of discrete self‐assembled collagen threads: Effects on mechanical strength and cell–matrix interactions

Abstract: Bundles of threads extruded from type I collagen have been researched extensively as scaffolds to promote the repair and regeneration of torn tendons and ligaments. The success of these scaffolds has been limited by insufficient tissue ingrowth from the wound margin, which may be inhibited by the chemical or physical crosslinking treatment used to increase the mechanical properties and decrease the degradation rate of these scaffolds. Recently, self-assembled collagen threads extruded from solutions of type I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
114
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 46 publications
4
114
0
1
Order By: Relevance
“…The present study tested these hypotheses using three cross-linking agents, genipin (GP), methylglyoxal (MG), and ultra-violet irradiation with photosensitizer riboflavin (UV). These agents were chosen due to their demonstrated potential to cross-link other collagenous tissues, [6][7][8]10,11 their potential to diffuse into tissue, 10 and their reported low toxicity. 9 Our experiments confirmed that GP, MG, and UV augment tissue mechanics on the fascicle level in a rat tail tendon model (RTTF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study tested these hypotheses using three cross-linking agents, genipin (GP), methylglyoxal (MG), and ultra-violet irradiation with photosensitizer riboflavin (UV). These agents were chosen due to their demonstrated potential to cross-link other collagenous tissues, [6][7][8]10,11 their potential to diffuse into tissue, 10 and their reported low toxicity. 9 Our experiments confirmed that GP, MG, and UV augment tissue mechanics on the fascicle level in a rat tail tendon model (RTTF).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, collagen cross-linking induced by irradiation with ultra-violet (UV) light has been reported in augmenting biomechanical properties of self-assembled collagen threads. 6 A similar procedure involving UV stiffening of the sclera has been clinically applied in patients for treatment of keratokonus. 7 Genipin (GP), a naturally occurring cross-linker derived from the gardenia fruit used in traditional Chinese medicine has successfully been applied to improve intervertebral disc strength and functional integrity in experimental models of disc degeneration.…”
mentioning
confidence: 99%
“…10 Under appropriate conditions, dehydrothermal (DHT) or ultraviolet light physical crosslinking can significantly improve scaffold strength without introducing cytotoxic chemicals as occurs with glutaraldehyde chemical crosslinking. 11,12 For example, Wang et al reported that exposing reconstituted collagen fibers to 5 days of DHT crosslinking at elevated temperatures increased tensile strength and modulus values. 13 Initial improvements in the structural and material properties of collagen fibers (e.g., by DHT crosslinking) will be critical to developing biodegradable materials that promote healing of orthopedic soft tissues.…”
mentioning
confidence: 99%
“…[10][11][12][13][30][31][32] If not applied appropriately, DHT crosslinking is well known to change the chemical composition of collagen-based membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation